A study on the edge chipping according to spindle speed and inclination angle of workpiece in laser-assisted milling of silicon nitride. (1st February 2018) - Woo, Wan-Sik; Lee, Choon-Man
Highlights: Laser-assisted milling (LAMill) of workpiece with inclination angle is performed. Edge chipping according to various machining conditions is investigated. LAMill is confirmed to be an effective method for machining silicon nitride. Effective machining conditions for improving tool life are confirmed. Abstract: Ceramics are difficult to machine due to their high hardness and brittleness. As an effective method for machining ceramics, laser-assisted machining (LAM) has been studied by many researchers. In particular, many studies of methods to improve the machinability of silicon nitride using LAM have been performed. However, there is little research on the effect of the inclination angle of the workpiece, because varying the angle increases the difficulty of controlling the laser preheating and tool path. This paper investigates the effect of preheating temperature, spindle speed and inclination angle of the workpiece on edge chipping of silicon nitride in an effort to obtain an enhanced surface finish using laser-assisted milling (LAMill). The machining conditions were determined by considering the parameters that can reduce edge chipping using related theory. Experimental results showed a reduction in edge chipping based on increases in preheating temperature, spindle speed and inclination angle of the workpiece. Also, by increasing the spindle speed and the inclination angle of the workpiece, surface roughness was decreased due to reduction in the cutting force. The energy efficiency of LAMill by comparing the specific cutting energy according to the machining conditions is analyzed.